Family Coaching terhadap Pelaksanaan Tugas Kesehatan Keluarga pada Klien Stroke - Ernawati Ernawati; Sovia Sovia; Debbie Nomiko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of family coaching on the implementation of family health tasks for stroke clients. This research method uses experimental research with a pretest-posttest control group design method. The results showed that the average score of the stroke client family health task implementation in the control group during the pre-test was 50.23 with a standard deviation of 5.217, while the post-test was 51.06 with a standard deviation of 3.162. The average score of the stroke client's family health task implementation in the intervention group at the pre-test was 48.09, with a standard deviation of 7.199. At the same time, the average score for implementing family health tasks during the post-test was 61.66, with a standard deviation of 1.578. The average score of the stroke client's family health task implementation in the control group was 51.06 with a standard deviation of 3.162, while in the intervention group, it was 61.66 with a standard deviation of 1.578. The results of statistical tests showed that the p-value <0.05. In conclusion, there is an effect of family coaching on the implementation of five family health tasks for stroke clients at home. Keywords: Family Coaching, Stroke, Family Health Tasks